Born to Manage : The Autobiography - Venables, Terry and Montgomery, Alex (London Simon and Schuster, 2014)
After a playing career that spanned more than 15 years, and took in golden spells in the sixties with Chelsea and Spurs, it was almost inevitable that Terry Venables would move into management. Following early success with Crystal Palace and Queens Park Rangers, he was appointed to the plum job of managing Barcelona, one of the biggest clubs in Europe. The Spanish giants had been struggling, but he soon turned them around and brought them trophy success, which inevitably earned him the nickname 'El Tel'. He returned to England to take charge of Spurs, where he helped save the club from financial troubles, and formed an ill-fated partnership with Alan Sugar. Again there was trophy success, as Venables worked with top England stars such as Paul Gascoigne, Gary Lineker and Chris Waddle, and when the England job fell vacant, he was the obvious choice for the role, leading the nation to the semi-finals of Euro 96 where they lost out on a place in the final after a penalty shoot-out. After leaving the England job, he has subsequently worked in numerous different roles. A charismatic and gregarious personality, Venables is widely viewed as one of football's great tacticians and is the most successful English manager of recent years. His story is sure to fascinate and entertain all followers of the game, providing a unique insight based on more than 50 years at the top.
Include Index and Illustration
Keywords: Venables, Terry. -- Soccer managers -- England -- Biography. -- Soccer managers -- Spain -- Barcelona -- Biography